1998
DOI: 10.1182/blood.v91.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ability of Bone Marrow Stromal Cells to Support B-Lymphopoiesis With Age

Abstract: B-lymphopoiesis decreases with age. We studied how aging affects bone marrow stromal cells, because they provide the growth factors and cell contacts required for B-lymphopoiesis. No differences were noted in the cell-surface phenotype of young and old primary-cultured stromal cells. Fluorescence-activated cell sorter-purified stromal cells from old mice were deficient in the ability to support the proliferation of interleukin-7 (IL-7)–specific B-lymphoid cell lines. The kinetics of this response indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(72 citation statements)
references
References 45 publications
6
65
0
1
Order By: Relevance
“…Two previous studies concluded that B lymphocytes are made continuously throughout life in human bone marrow (55,57). This contrasts to the situation in mice where some investigators concluded that lymphopoietic activity is greatly reduced in old animals (66)(67)(68). While numbers of B-cell precursors within a given bone can be easily assessed in the mouse, absolute values are difficult to obtain for human bone marrow.…”
Section: B Cells Are Indeed Made Throughout Life In Humansmentioning
confidence: 98%
“…Two previous studies concluded that B lymphocytes are made continuously throughout life in human bone marrow (55,57). This contrasts to the situation in mice where some investigators concluded that lymphopoietic activity is greatly reduced in old animals (66)(67)(68). While numbers of B-cell precursors within a given bone can be easily assessed in the mouse, absolute values are difficult to obtain for human bone marrow.…”
Section: B Cells Are Indeed Made Throughout Life In Humansmentioning
confidence: 98%
“…123 Additionally, IL-7 receptor components seem to be expressed in Pro-and B cells derived from old mice at comparable levels to young mice. 124 Thus, IL-7 therapy alone might not work because of the inability to maintain this cytokine in the particular niche and/or signalling defects in the aged mice. In fact phosphorylated P-STAT5, a signal transducer from IL-7 and IL-2 receptor JAK activation, is likely to be crucial in anti-immunosenescence therapies because its presence is much reduced in both aged B-cell precursors 40 and ageing T cells.…”
Section: Age-dependent Defects In Peripheral T Cellsmentioning
confidence: 99%
“…This finding suggests that part of the deficiency observed in macrophages from aged animals and humans might be caused by changes in the tissue environment. It is known that the stromal environments of the bone marrow, the spleen, the lymph nodes and the thymus change with age, resulting in reduced hematopoiesis, thymopoiesis, and peripheral homeostasis (1)(2)(3)(4)(5)(169)(170)(171)(172)(173)(174)(175)(176). Although myeloid dendritic cells in aged rodents and humans appear to be poorly immunogenic (8,10,141,142), fully functional myeloid dendritic cells can be generated in vitro from blood monocytes from aged donors (177).…”
Section: Apoptotic Cellsmentioning
confidence: 99%